Forage vegetation for stingless bees to support the sustainability of the meliponiculture in Tulak Tallu Village, South Sulawesi, Indonesia - SYAMSUDDIN MILLANG; BUDIAMAN BUDIAMAN; YENI OKTAVIA; ANDI PRASTIYO; ENY YUNIATI (Society for Indonesian Biodiversity, 2026)
Abstract. Millang S, Budiaman, Oktavia Y, Prastiyo A, Yuniati E. 2026. Forage vegetation for stingless bees to support the sustainability of the meliponiculture in Tulak Tallu Village, South Sulawesi, Indonesia. Biodiversitas 27 (1): d270124. https://doi.org/10.13057/biodiv/d270124. The stingless bee is an insect that plays a crucial role in pollinating various flowering plants in tropical ecosystems. However, forage resource management remains limited because previous studies have focused mainly on the importance value index (IVI) without integrating flowering calendars and actual foraging activity. This study aims to identify forage plant species for stingless bees as a basis for better feed planning. Sampling was conducted across all vegetation growth strata from April to May 2024. Interviews, field data collection, and literature studies were conducted to record the flowering period. The results identified 39 plant species from 25 families as potential food sources. Vegetation analysis showed that the species with the highest IVI at each growth stage were coconut (Cocos nucifera) at the tree level (IVI = 55.20), jackfruit (Artocarpus heterophyllus) at the pole level (IVI = 48.53), calliandra (Calliandra calothyrsus) at the sapling level (IVI = 53.21), and goad weed (Ageratum conyzoides) at the seedling level (IVI = 29.79). The combination of multi-strata vegetation with asynchronous flowering patterns plays a role in maintaining the continuity of bee food availability throughout the season at the study site. These findings indicate that several types of plants around meliponiculture need to be identified to see the vegetation that is a food source for the continued development of bee colonies, especially at the research location.